(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Nanoparticles are becoming an increasingly important aspect of the technological infrastructure of today. Copper oxide nanoparticles are extremely useful, as well as their application has grown across a wide variety of fields thanks to their adaptability. In this review, we present a variety of techniques for synthesizing copper oxide nanoparticles. By reason of their electric, catalytic, photonic, optical, as well as antibacterial features, copper oxide nanoparticles have garnered considerable attention. In recent years, the utilization of nanocrystalline semiconductor particles has increased due to their elevated ratio of surface area to volume as well as distinctive photovoltaic features. This pattern has been observed in multiple recent years.